PENGARUH ABILITY, BENEVOLENCE DAN INTEGRITY TERHADAP TRUST, SERTA IMPLIKASINYA TERHADAP PARTISIPASI PELANGGAN E-COMMERCE: STUDI KASUS PADA PELANGGAN E-COMMERCE DI UBM - Wong, David (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
This research aims at analyzing (1) the effect of vendor’s ability, benevolence, and integrity variables toward e-commerce customers’ trust in UBM; (2) the effect of vendor’s ability, benevolence, and integrity variables toward the level of e-commerce customers’ participation in Indonesia; and (3) the effect of trust variable toward level of e-commerce customers participation in UBM. This research makes use of UBM e-commerce users as research samples while using Likert scale questionnaire for data collection. Furthermore, the questionnaires are sent to as many as 200 respondents. For data analysis method, Structural Equation Model was used. Out of three predictor variables (ability, benevolence, and integrity), it is only vendor’s integrity that has a positive and significant effect on customers’ trust. On the other hand, it is only vendor’s integrity and customer’s trust that have a positive and significant effect on e-commerce customers’ participation in UBM. Keywords: e-commerce customers’ participation, ability, benevolence, integrity